Latex Agglutination Test for Early Detection of Causative Organism in Acute Bacterial Meningitis - Mishra, B; Mahaseth, C; Rayamajhi, A (Journal of Nepal Paediatric Society, 2013)
Introduction: Acute bacterial meningitis is one of the leading causes of mortality and morbidity in children. Identification of the causative organism is crucial to its management and outcome. The objective of this study was to see the usefulness of latex agglutination test in the early diagnosis of acute bacterial meningitis. Materials and Methods: A hospital based prospective cross-sectional study was conducted at Kanti Children’s Hospital during December 2004 to August 2005. Cerebrospinal fluid from 150 consecutive clinically suspected cases of acute bacterial meningitis between the age group of 2 months to 14 years were analyzed. Bacterial culture and latex agglutination test was done on cerebrospinal fluid obtained from all 150 suspected cases of acute bacterial meningitis. Latex agglutination test was done using the BD DirectigenTM Meningitis Combo test kit (Becton, Dickinson and company, USA) for Streptococcus pneumoniae, group B Streptococcus, Escherichia coli, Neisseria meningitidis group A,C and Y/ W135, and Hemophilus influenzae type b. Data was analysed by using SPSS Version 11.5. Results: Of the 150 Cerebrospinal fluid samples analysed bacterial culture identified only 4 meningitis cases giving an isolation rate of 1.3% whereas latex agglutination test identified 29 cases giving an isolation rate of 19.3% from 150 samples. Streptococcus pneumoniae, Hemophilus influenzae type b and Group B Streptococcus were the most common causative organism. Conclusion: Latex agglutination test has a better yield, higher sensitivity, provides microbiological diagnosis earlier than the traditional cerebrospinal fluid culture and is easy to perform. DOI: http://dx.doi.org/10.3126/jnps.v33i1.7047 J Nepal Paediatr Soc. 2013;33(1):34-38